2001
DOI: 10.1021/nl015519n
|View full text |Cite
|
Sign up to set email alerts
|

Albumin−CdTe Nanoparticle Bioconjugates:  Preparation, Structure, and Interunit Energy Transfer with Antenna Effect

Abstract: Conjugates of bovine serum albumin and CdTe nanoparticles capped with l-cysteine have been synthesized via a one-pot glutaric dialdehyde cross-linking procedure. Diads (1:1) with some amount of 2:1 albumin−nanoparticle assemblies preferably form in this reaction, as evidenced by gel electrophoresis. Circular dichroism spectroscopy demonstrates that the tertiary structure of the protein remains largely intact after the conjugation. Attachment of protein moieties result in a significant increase of CdTe emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
322
1
8

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 418 publications
(334 citation statements)
references
References 43 publications
3
322
1
8
Order By: Relevance
“…Research in semiconducting nanoparticles is one of the most investigated subjects, due to their wide field of applications. Recently, the surface modification of fluorescent semiconductor nanoparticles by biomolecules and nucleic acids, has added a new dimension to nanoparticle research, with respect to their biological applications (Mamedova et al 2001). This article deals with the preparation of CdS nanoparticles using the wet chemical method.…”
Section: Introductionmentioning
confidence: 99%
“…Research in semiconducting nanoparticles is one of the most investigated subjects, due to their wide field of applications. Recently, the surface modification of fluorescent semiconductor nanoparticles by biomolecules and nucleic acids, has added a new dimension to nanoparticle research, with respect to their biological applications (Mamedova et al 2001). This article deals with the preparation of CdS nanoparticles using the wet chemical method.…”
Section: Introductionmentioning
confidence: 99%
“…6,[19][20][21][22][23][24] During conjugation of bare CdTe nanoparticles to BSA, it was concluded that encapsulation was necessary to prevent particle growth, photoinduced decomposition, and conjugate aggregation. 13 Amorphous silica shells have been shown to provide some prime advantages necessary for bioconjugation of QDs. First, the silica shell prevents flocculation of particles, prevents species from adsorbing onto the surface, and helps to maintain the photoluminescence.…”
Section: Introductionmentioning
confidence: 99%
“…In a typical synthesis [26][27], 5 mmol of CdCl 2 .2.5H 2 O was dissolved in 110 mL of water, and 12 mmol of TGA were added under stirring, followed by adjusting the pH to 11 by dropwise addition of 1 M NaOH solution. The mixed solution was placed in a three-necked flask deaerated by N 2 bubbling for 30 min.…”
Section: Preparation and Characterization Of Mqdsmentioning
confidence: 99%